Patan-Vãbāhā History and Inventory of a Newar Buddhist Monastery - Basukala, Bijay (Documenta Nepalica - Book Series, 2022)
This volume presents the religious, architectural, and textual background of Vãbāhā, one of the 16 main monasteries of Patan, located in one of the three royal cities of the Kathmandu Valley in Nepal. The history of the Buddhist monastic courtyard and its objects is presented along with 42 inscriptions, dating from 1596 CE to 2021.